Fatigue and depression improvements on breast cancer survivors practitioners of strength training - Sandro Nobre Chaves; Filipe Dinato de Lima; Brenda Búrtuli Perondi; Jaqueline Vieira; Julia de Morais Elias; Leonardo Amorim Ribeiro; Achilles Khaluf Soares Silva; Sacha Clael; Ricardo Jacó de Oliveira (Universidade Federal de Santa Catarina, 2021)
Due to the high incidence of breast cancer worldwide, it's important to research and understand the physiological and psychological effects of this disease, like fatigue, depression and capacity to do daily life tasks and how they modify physical activity. The aim of this present study was to analyze the effects of strength training practice on physical fatigue (IMF-20), depression (Beck questionnaire), handgrip strength and functional performance (time up and go). The sample was composed by 17 women breast cancer survivors, in which 8 volunteers were strength training practitioners for at least 6 months (P), and 9 volunteers were non-practitioners (NP). The T-test identified significant differences (p>0,05)  between groups on fatigue (P=7,37±1,76; NP= 10,77±3,41; p=0,02) and on depression (P= 8,75±5,20; NP= 14,55±4,21). There was no significant difference between groups on handgrip strength and functional performance.